Economic and environmental impacts of raising revenues for climate finance from public sources - Christoph Böhringer; Jan Schneider; Marco Springmann (University of Oldenburg, Department of Economics, 2017)
In response to anthropogenic climate change, developed countries have committed themselves to raise 100 billion USD a year from 2020 onwards for addressing the needs of developing countries. In this paper, we investigate the economic and CO2 emission impacts of four alternative options for raising climate funds from public sources in developed countries: CO2 emission prices, wires charges on electricity consumption, a tax on international transport services, and the removal of fossil fuel subsidies. We find that these four options do not only induce very different global costs to raise given amounts of climate funds but have quite diverging implications for the cost incidence between developed and developing countries. Likewise, the global CO2 emission impacts of alternative fund-raising policies differ a lot.
Keywords: C68; Q58; 330; climate finance; computable general equilibrium; green climate fund